Influence of target composition and deposition temperature on the domain structure of BiFeO3 thin films - Motapothula, M. (2013)
Domain structure of BiFeO3 thin films can be controlled by adjusting the target composition or the substrate temperature during pulsed laser deposition. Decreasing Bi content in the target or increasing substrate temperature changes the domain structure of BiFeO3 from 71° to 109°. We suggest that a combination of interface effect and defect induced internal field causes this evolution.